2015
DOI: 10.1088/0031-9155/60/2/807
|View full text |Cite
|
Sign up to set email alerts
|

Sparse representation and dictionary learning penalized image reconstruction for positron emission tomography

Abstract: Accurate and robust reconstruction of the radioactivity concentration is of great importance in positron emission tomography (PET) imaging. Given the Poisson nature of photo-counting measurements, we present a reconstruction framework that integrates sparsity penalty on a dictionary into a maximum likelihood estimator. Patch-sparsity on a dictionary provides the regularization for our effort, and iterative procedures are used to solve the maximum likelihood function formulated on Poisson statistics. Specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…Specifically, authors in [12] proposed an adaptive dictionary learning approach for PET image deblurring while suppressing Poisson noise effects. In [13], a reconstruction framework integrating SR and DL into a maximum likelihood estimator has been proposed for accurate and robust PET image reconstruction. Besides, dual dictionary learning has been successfully applied to biomedical imaging as well [1416].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, authors in [12] proposed an adaptive dictionary learning approach for PET image deblurring while suppressing Poisson noise effects. In [13], a reconstruction framework integrating SR and DL into a maximum likelihood estimator has been proposed for accurate and robust PET image reconstruction. Besides, dual dictionary learning has been successfully applied to biomedical imaging as well [1416].…”
Section: Introductionmentioning
confidence: 99%
“…3) Other Applications and Variations: Later works applied dictionary learning to dynamic MRI [28], [115], [116], parallel MRI [117], and PET reconstruction [118]. An alternative Bayesian nonparametric dictionary learning approach was used for MRI reconstruction in [119].…”
Section: B Synthesis Dictionary Learning-based Approaches For Reconsmentioning
confidence: 99%
“…We conclude that our dictionary-based reconstruction method appears to have an edge over the other three methods. Our formulation in (8) enforces that the solution is an exact representation in the dictionary, and searching for solutions in the cone spanned by the dictionary elements is a strong assumption in the reconstruction formulation. In [33] we investigated this requirement experimentally and showed that relaxing the equality Πx = (I ⊗ D) does not give an advantage, i.e., approximating a solution by Πx ≈ (I ⊗ D)α and minimizing Πx − (I ⊗ D)α 2 does not improve the reconstruction quality, and one can compute a good reconstruction as a conic combination of the dictionary elements.…”
Section: Studies Of the Reconstruction Stagementioning
confidence: 99%
“…Imposing both non-negativity and a 1-norm constraint on the representation vector α are strong assumptions in the reconstruction formulation. If we drop the non-negativity constraint in the image reconstruction problem, then (8) takes the form of a constrained least squares problem:…”
Section: Simplifying the Computational Problemmentioning
confidence: 99%